the Efektivitas Layanan Bimbingan Kelompok dengan Teknik Permainan terhadap Keterampilan Komunikasi Antar Pribadi Siswa Kelas X MIPA 1 Sma Negeri Colomadu - Paramesthi, Anggi; Suryanti, Hera Heru Sri; Jawandi, Ahmad (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
The purpose of this study was to determine the effectiveness of group guidance services with game techniques on interpersonal communication skills of class X MIPA 1 students of SMA Negeri Colomadu in the 2021/2022 academic year. This research is an experimental quantitative research. The population of this study were students of class X MIPA 1 SMA Negeri Colomadu in the academic year 2021/2022 which collected 36 students. The sample in this study used all students of class X MIPA 1 SMA Negeri Colomadu in the academic year 2021/2022 which involved 36 students, so the sampling technique used was nonprobability sampling with saturated sampling, which used all members as samples. The data collection tool in this study used a questionnaire as the main method and documentation as an auxiliary method. To analyze the data using the t-test formula. Based on the results of data analysis, the value of tcount = 7,194 was then compared with ttable at d.b = N - 1 (36 - 1) = 35, which showed ttable at a significance level of 1% = 2.724 and 5% = 2.030. Thus, it can be said that tcount is greater than ttable at the 1% and 5% significance levels, namely 2,724 < 7.194 > 2,030. In connection with these results, then H0 which reads "Group guidance services with game techniques are not effective on interpersonal communication skills of class X MIPA 1 students at SMA Negeri Colomadu in the 2021/2022 academic year" are not proven true and Ha is accepted which reads "Group guidance services with effective game techniques on interpersonal communication skills of students of class X MIPA 1 SMA Negeri Colomadu in the academic year 2021/2022" proved to be true.